EVALUATING THE PRAGMATIC PARTICLE JÃ‚â€™ IN A MADURESE SPOKEN CORPUS - Irham, Irham (Indonesian Journal of Applied Linguistics, 2018)
In verbal interaction and communication, speakers often employ communicative signals; verbal or non-verbal, special words or phrases, which can be regarded as pragmatic markers (Fraser, 1996; Foolen 2011). This paper aims to investigate the Madurese pragmatic particle jÃ¢â€™: its position in the sentence and in sequences of interaction, and how it functions in conversation. To achieve the objectives of the present study, conversation analysis was employed to describe the particleâ€™s position in interaction and to account for its pragmatic functions. The data of the present study were taken from recorded conversations among Madurese speakers. This study showed that the particle jÃ¢â€™ predominantly occurred in turn-initial positions. In addition, the particle jÃ¢â€™ also appeared in sentence-initial and sentence-middle positions but not in sentence-final positions. In terms of function, the particle jÃ¢â€™ could function as topic shifts, prohibitive markers, and emphatic markers.